Baseline incidence of adverse birth outcomes and infant influenza and pertussis hospitalisations prior to the introduction of influenza and pertussis vaccination in pregnancy: a data linkage study of 78 382 mother–infant pairs, Northern Territory, Australia, 1994–2015. (2019) - McHugh, L.; Andrews, R.M.; Leckning, B.; Snelling, T.; Binks, M.J.
Abstract: We conducted probabilistic data linkage of three population datasets for the Northern Territory (NT), Australia, to describe the incidence of preterm births, stillbirths, low birthweight and small for gestational age (SGA) per 1000 NT births; and influenza and pertussis hospitalisations per 1 00 000 NT births in infants <7 months of age, in a pre-maternal vaccination era. The Perinatal Trends dataset (1994–2014) formed the cohort of 78 382 births. Aboriginal mother–infant pairs (37%) had disproportionately higher average annual rates (AR) for all adverse birth outcomes compared to their non-Aboriginal counterparts; rate ratios: preterm births 2.2 (AR 142.4 vs. 64.7); stillbirths 2.3 (AR 10.8 vs. 4.6); low birthweight 2.9 (AR 54 vs. 19); and SGA 1.7 (AR 187 vs. 111). Hospitalisation (2000–2015) and Immunisation Register datasets (1994–2015), showed that influenza hospitalisations ( n = 53) and rates were 42.3 times higher in Aboriginal infants (AR 254 vs. 6); and that pertussis hospitalisations ( n = 37) were 7.1 times higher in Aboriginal infants (AR 142.5 vs. 20.2) compared to non-Aboriginal infants. These baseline data are essential to assess the safety and effectiveness of influenza and pertussis vaccinations in pregnant women from the NT. Remote living Aboriginal women and infants stand to benefit the most from these vaccines.